Two-photon polarization microscopy reveals protein structure and function - Lazar, Josef; Bondar, Alexey; Timr, Stepan; Firestein, Stuart J (Nature methods, 2011)
Membrane proteins are a large, diverse group of proteins, serving a multitude of cellular functions. They are difficult to study because of their requirement of a lipid membrane for function. Here we show that two-photon polarization microscopy can take advantage of the cell membrane requirement to yield insights into membrane protein structure and function, in living cells and organisms. The technique allows sensitive imaging of G-protein activation, changes in intracellular calcium concentration and other processes, and is not limited to membrane proteins. Conveniently, many suitable probes for two-photon polarization microscopy already exist.
Keywords: polarizační mikroskopie; Membrane Proteins; Structure-Activity Relationship; Cell Membrane; konformace proteinů; Microscopy, Polarization; Protein Conformation; membránové proteiny; buněčná membrána; vztahy mezi strukturou a aktivitou; mikroskopie fluorescenční multifotonová; Microscopy, Fluorescence, Multiphoton